Unravelling the Drivers of Purchase Intention towards Electric Cars in England - Tyagi, Satyarth (2024)
The electric car market in England has experienced notable growth, spurred by government initiatives, an expanding charging infrastructure, and increased automakers’ commitments. The market is evolving quickly, emphasizing infrastructure development and a broader range of electric vehicle options. The push for electric vehicles aligns with the broader environmental goals of reducing air pollution and carbon emissions, contributing to the United Kingdom's commitment to a more sustainable transportation sector. As interesting as it would be to watch heritage brands marry their distinct styles with electric capabilities, a loyal customer base might not be enough leverage for a foray into the electric car industry. This thesis investigates the factors influencing the purchase intention of electric cars among English consumers. Grounded in Rational Choice Theory, the study examines six key factors: driving range, charging infrastructure, purchase cost, government incentives, environmental awareness, and perceived social influence. This research employs a quantitative approach, utilizing a survey instrument to investigate the aforementioned topic. Data was collected through 114 online questionnaires administered to English consumers. Subsequently, a regression analysis was conducted using SPSS software to examine the influence of the six identified determining factors. As a result of the study, it was revealed that focusing on environmental and social aspects might be particularly effective in driving purchase intention for electric cars. The findings indicated a significant shift in consumer priorities compared to the past decade.